The illustrated Bulfinch's Mythology. The legends of Charlemagne - Bulfinch, Thomas, 1796-1867 (Macmillan USA, 1997)
The legends of Charlemagne and his Paladins, blending fact and fancy, are recounted in the stories of their resistance to the Infidel invasions of Europe during the middle ages. Includes tales of Roland, Bradamante the female kight, the Hippogriff, Durindand the magic sword, Rogero the Moor, and the treacherous Ganelon.